Enhancing Early Childhood Cultural Education through the Ponorogo Reyog Theater Suitcase: A Development and Evaluation Study - Fatimah, Siti; Hermanto (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2024)
This research explores the Reyog Theater Suitcase (Koper Teater Reyog) as an innovative educational tool for introducing the cultural heritage of Ponorogo to early childhood education. Utilizing a Research and Development (R&D) approach and the ADDIE model, which includes the Analyze, Design, Development, Implement, and Evaluation stages, the study employed a Posttest-only experimental design with nonequivalent groups. An initial needs analysis revealed a scarcity of practical storytelling media that incorporate local narratives, such as Reyog Ponorogo, despite its prevalence in local education. Consequently, the Reyog Theater Suitcase was developed, featuring a transparent display panel, barcode-activated musical features, and manageable cultural figurines. Data collection involved expert validation through questionnaires, teacher surveys, and authentic assessments using qualitative and quantitative analyses. The findings indicated that classes using the Reyog Theater Suitcase achieved significantly better outcomes in cultural education than traditional picture books. After two rounds of feedback and revisions from experts, the quality and educational appropriateness of the product were enhanced. Hypothesis testing in both small and large-scale settings resulted in p-values of 0.000 and 0.002, respectively, leading to the rejection of the null hypothesis and acceptance of the alternative hypothesis; this confirmed that the experimental group exposed to the Reyog culture through the suitcase differed significantly from the control group using conventional media. Integrating physical and digital storytelling elements advances the discourse on delivering educational content in the digital era. However, focusing on a specific cultural narrative might limit its application to similar educational settings. Further research is recommended to evaluate its broader applicability in diverse educational environments. This study underscores the importance of innovative storytelling media that integrate local cultures, offering potential pathways to enrich global early childhood education.